Readings of Kant's "Anticipations of Perception": The Origin of the Philosophies of Intensity - Merino Mora, Alejandra (2025)
The Kantian table of categories in the Critique of Pure Reason, which posits the a priori conditions of possible experience, has been subject to recurrent criticism regarding its perceived inability to account for the dynamic and contingent nature of empirical experience. This paper undertakes an analysis of the category of quality, as articulated in the «Anticipations of Perception» section, to demonstrate how Kant, by integrating the advancements of infinitesimal calculus and its treatment of variable magnitudes, provides a framework for reevaluating the transcendental apparatus. It is argued that this opening within the transcendental system informed the philosophies of Maimon, Cohen, and Deleuze, who aimed to modify the initial categorial rigidity and enable the transcendental to function as an «intensive spatium». Through a critical examination of the «Anticipations», it is shown that transcendental schematism, rather than being a rigid mechanism of object constitution, can accommodate elements of a «logic of emergence», wherein contingency, non-linear temporality, and intensity play constitutive roles. Consequently, the analysis of the category of quality reveals the hitherto underappreciated plasticity of the Kantian categorial system.